Career Development of Chinese Canadian Professional Immigrants. Issue 3 (September 2016) - Chen, Charles P.; Hong, Julie Wai Ling
Abstract : Chinese professional immigrants make up the 2nd largest visible minority group in Canada. Their successful resettlement in the host country is inextricably tied to the prosperity and success of the general Canadian society that depends heavily on its immigration practice for the country's development and growth. However, there is a dearth of literature and research on this particular population, especially in the areas of career development and vocational psychology based on the unique cultural context of Canada. To address the pivotal career needs of Chinese professional immigrants, this article identifies and discusses 6 prominent career‐related barriers they face in the resettlement process: migration‐related stressors; language proficiency; cultural nuances and knowledge; discrimination and prejudice; foreign‐earned experiences, education, and credentials not recognized; and family separation and fragmentation. Strategies to tackle these career development barriers are proposed from a life‐career integrated perspective, alongside ideas and strategies for effective career interventions.